Detection of Histamine-Producing Bacteria on Tuna Species using Histidine Decarboxylase (hdc) and 16S rRNA - Mala Nurilmala; Novia Nanda Saputri; Asadatun Abdullah; Nurjanah Nurjanah; Roza Yusfiandayani; Muhamad Fedi Alfiadi Sondita (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2020)
Histamine-producing bacteria to predict histamine level production can be identified by a molecular approach. The purpose of this study was to identify the types of histamine-producing bacteria on tuna, little tuna, and skipjack (TTC) meat, to analyze its bioinformatics through phylogenetic tree construction also to determine the levels of its histamine. The identification of histamine-producing bacteria was conducted using a molecular technique based on the hdc and 16S rRNA genes. Histamine levels were measured by a spectrofluorometer. The results showed types of histamine-producing bacteria had been successfully identified, both using specific hdc and 16S rRNA universal primers, including Morganella morganii, Enterobacter hormaechei, Klebsiella aerogenes, and Enterobacter bugandensis. The phylogenetic tree showed that the bacteria M. morganii and E. hormaechei were closely related to one cluster. Meanwhile, the other close relative cluster were Klebsiella aerogenes, Enterobacter bugandensis, and Escherichia fergusonii. In addition, histamine levels of frozen tuna, little tuna, and skipjack were 2.96±0.22 ppm, 2.14±0.23 ppm, and 1.02±0.97 ppm, respectively.